Development of Interactive PowerPoint Media to Improve Science Learning Outcomes of Grade V Students of SDN 2 Gumulan Academic Year 2024/2025 - Nova Sugiana Purwaningrum; Isna Rahmawati; Nela Rofisian (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to create and evaluate interactive PowerPoint learning media used to help fifth grade students at SDN 2 Gumulan to understand lessons more easily and improve learning outcomes. The problems faced are low learning motivation and monotonous teaching methods for science. As a solution, interactive PowerPoint media is used for fifth grade science material, Chapter 6 "Indonesia is Rich" with the topic "How is My Indonesia?". This study uses the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The results of the study showed that this media was very feasible to use, with a feasibility value of 92% from material experts and 88% from media experts. This media has also proven effective because it can increase student learning scores by 65% ​​from pre-test to post-test. In addition, students feel more enthusiastic and interested when learning using this media. However, this study still has shortcomings, such as only being conducted in one school, only covering one topic, and the time is short. For this reason, further research is needed with more participants and a longer time so that the results are stronger and more comprehensive.